2009
DOI: 10.1590/s1517-86922009000700014
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção primária de doenças cardiovasculares na obesidade infantojuvenil: efeito anti-inflamatório do exercício físico

Abstract: A pandemia da obesidade juvenil e do sedentarismo está relacionada com o maior risco de doenças cardiovasculares no futuro. Ambas com fisiopatologia inflamatória, essas condições têm atraído significativa atenção científica. O início dos eventos que agridem o endotélio vascular pode ocorrer na infância, porém, sinais clínicos da aterosclerose geralmente só aparecem na fase adulta. O tecido adiposo é hoje reconhecido por seu papel ativo, induzindo a produção de citocinas pró e anti-inflamatórias, como o fator d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
4
0
5
Order By: Relevance
“…Regarding the type of school, 66% reported public schools, corroborating the findings of Rossetti et al (2009) [18], who identified an even higher percentage in their research, 80%. The fact that this study included children and adolescents attended in a public specialized service with predominance of low family income can explain this high percentage.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the type of school, 66% reported public schools, corroborating the findings of Rossetti et al (2009) [18], who identified an even higher percentage in their research, 80%. The fact that this study included children and adolescents attended in a public specialized service with predominance of low family income can explain this high percentage.…”
Section: Discussionsupporting
confidence: 78%
“…(1,3,9) Furthermore, the prevalence of sedentarism in university students demand the investigation of their association with other cardiovascular risk factors considering the contribution of physical activity to reduce blood glucose levels and blood pressure, increasing the level of HDL-cholesterol, lowering body weight, reducing all-cause mortality. (3,16,17) The results showed especially the need for orientation and stimulation for physical activity practice throughout the undergraduate course in nursing with a view to its application in everyday life of students. The high prevalence of sedentarism in seniors suggested that the process of nursing education has failed to encourage good results in the modification of students' lifestyle.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, despite a growing number of studies that analyzes the action and effectiveness of the PA and exercise on cardiometabolic markers in obese adolescents [9][10][11][12]14,15 . Also, there are few studies of systematic review describing intervention procedures with PA in cardiometabolic markers and risk factors of CVD in adolescents.…”
Section: Resumo O Acúmulo De Gordura Corporal é Um Dos Principais Fatmentioning
confidence: 99%
“…The lipoprotein lipase enzyme (LPL) controls fat stock, and PA increases the ability to release and storage energy of adipose tissue, as the capacity of carbohydrates and fat oxidation from muscle. The adipocytes excess in bloodstream, is related to the metabolic syndrome factors, and produce cytokines tumor necrosis factor α (TNF-α) and Interleukin-6 (IL-6) 14 .…”
Section: Introductionmentioning
confidence: 99%